A Lion's Trail - Verster, François (Jawitz, Dan ; Kaplan, Mark J. ; Verster, François, 2002)
"The Lion Sleeps Tonight” is one of the most recognizable pop songs in the world. But how many people realize that this American hit tune was actually written by Solomon Linda, a Zulu musician who never earned a cent in royalties and died in poverty? A LION'S TRAIL traces the music back to its original source, telling the story of how the Zulu song "Mbube" was transcribed by American folk singer Pete Seeger into "Wimoweh," finally gaining international recognition as "The Lion Sleeps Tonight." Verster began work on this film in 1999, when a South African TV show asked him to make a film about how “The Lion Sleeps Tonight” originated as an African song "Mbube"—a fact that came as a surprise to him. Once Verster began researching the original composition, he quickly became fascinated with the story behind the music. A friend gave him an audiocassette from Pete Seeger’s nephew that contained 21 versions of the same song. Verster was amazed at how these variations could all be traced back to Linda’s original four-chord tune. While exploring the moral and legal issues around the song, A LION'S TRAIL is also a vibrant and joyous celebration of the heritage of African music. Versions of the song are performed by musicians across the globe, including the Manhattan Brothers, Solomon Linda's daughters, Pete Seeger and Ladysmith Black Mambazo, who lead the Church of God in Africa in the South African town of Clermont. By combining stunning visuals with powerful musical performances, A LION’S TRAIL not only opens up the debate surrounding the origins of “Mbube” itself, but also reveals the controversies regarding copyright and ownership in the global music industry.